Trends in Stem Cell Biology and Technology - Baharvand, Hossein. (Humana Press, 2009)
The study of stem cell research has recently gained the attention from a growing, multidisciplinary community of scientist; this exponential growth of interest is driven by the hope of discovering cures for several diseases through transplantation medicine. Trends in Stem Cells Biology and Technology aptly serves this developing community as it reveals new aspects of stem cell research by specifically covering studies focused on spermatogonial stem cells, uniparental embryonic stem cell lines, the generation of gametes from stem cells, reprogramming germ cells to stem cells, nuclear and somatic cell genetic reprogramming, tissue engineering and mechanotransduction of stem cells and finally the development of stem cell technologies for the treatment of deafness, heart disease, corneal injury and diabetes. With contributions by leading scientists and renowned scholars, Trends in Stem Cells Biology and Technology offers a wide audience cutting edge information at a crucial time in this ever expanding field.